2018
DOI: 10.29271/jcpsp.2018.09.s204
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Lesion: Extralobar Sequestration With Cystic Adenomatoid Malformation – Misdiagnosed As Pulmonary Tuberculosis

Abstract: We report a rare case of bronchopulmonary extralobar sequestration in a 9-year girl mimicking pulmonary tuberculosis. Patient had recurrent chest infections and two episodes of massive hemoptysis. Preoperative x-ray chest showed an opacity in left lower lobe and computed tomography-aortogram showed that the lesion had systemic arterial supply from celiac trunk. Diagnosis of pulmonary sequestration was made and left lateral muscle sparing thoracotomy was planned. Intraoperatively, extralobar sequestration was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…2,3 From the literature review performed, these lesions usually tend to be symptomatic during the neonatal or infancy period and rarely present during childhood. 4,5,6,7,8,9 However Pierre Goussard et al 10 and Fatima Naumeri et al 11 , reported hybrid lesions in older children, who presented with lung infection, similar to our case. Therefore, a hybrid lung lesion should be kept in mind as a differential diagnosis in children presenting with recurrent pneumonia.…”
Section: Discussionsupporting
confidence: 86%
“…2,3 From the literature review performed, these lesions usually tend to be symptomatic during the neonatal or infancy period and rarely present during childhood. 4,5,6,7,8,9 However Pierre Goussard et al 10 and Fatima Naumeri et al 11 , reported hybrid lesions in older children, who presented with lung infection, similar to our case. Therefore, a hybrid lung lesion should be kept in mind as a differential diagnosis in children presenting with recurrent pneumonia.…”
Section: Discussionsupporting
confidence: 86%
“…In all our patients, the histopathological analysis of resected IDEPS showed hybrid lesions with CPAM elements, with rhabdomyomatous dysplasia in one. As shown also by our series of CLM, CPAM elements are more frequently associated to ILS then ELS ( 10 , 20 26 ). Hybrid lesions are defined carrying features of CPAM (both at histology and at imaging evaluation) within a portion of pulmonary tissue separate from the airways (BPS) and anomalous blood supply.…”
Section: Discussionsupporting
confidence: 78%
“…Bronchial atresia (BA) typically occurs near the central area of the lung, most commonly in the left upper lobe of the lung, and bronchial mucus plugs are often seen in the distal atresia segment. BA is a well-accepted abnormality in the majority of congenital cystic lung lesions [17,18,21]. BA refers to a lack of communication between the central airway and segmental or subsegmental bronchus.…”
Section: Discussionmentioning
confidence: 99%